A passive cooling wind catcher with heat pipe technology: CFD, wind tunnel and field-test analysis. (15th January 2016) - Calautit, John Kaiser; Hughes, Ben Richard
Graphical abstract: Highlights: A cooling wind tower incorporating heat pipe technology and cool sink was proposed. A cooling potential of up to 12 °C of air streams was identified in this study. Significant reduction in the temperature was observed at lower wind speeds (1–2 m/s). The system met the recommendation (10 L/s/person) for a wind speed of 2 m/s and higher. Field testing was carried out in Ras Al Khaimah, UAE to evaluate its performance under real operating conditions. Abstract: Wind catchers are natural ventilation systems based on the design of traditional architecture, intended to provide ventilation by manipulating pressure differentials around buildings induced by wind movement and temperature difference. Though the movement of air caused by the wind catcher will lead to a cooling sensation for occupants, the high air temperature in hot regions will result in little cooling to occupants. In order to maximise the properties of cooling by wind catchers, heat pipes were incorporated into the design. Computational Fluid Dynamics (CFD) was used to investigate the effect of the cooling devices on the performance of the wind catcher, highlighting the capabilities of the system to deliver the required fresh air rates and cool the ventilated space. Qualitative and quantitative wind tunnel measurements of the airflow through the wind catcher were compared with the CFD data and good correlation was observed. Preliminary field testing of the wind catcher was carried out to evaluate its thermal performance under real operating conditions. A cooling potential of up to 12 °C of supply air temperature was identified in this study.